A "Dictionary of locutons from liturgical books" by protopriest A. I. Nevostruev - Maria Davydenkova; Maria Strievskaya; Nadezhda Kaluzhnina; Olga Strievskaya (Вестник Православного Свято-Тихоновского гуманитарного университета: Сериа III. Филология)
The Dictionary of words from liturgical books” by Archpriest A. Nevostruev which was completed in the middle of the XIXth century and has never been published can be regarded both as a significant achievement of Church Slavonic studies and a unique lexicographic source. The manuscript can be found in Russian State Library. The manuscript’s conditions predetermined the necessity of complex preliminary research and editorial efforts. The significance of the planned study is in introduction of the text previously almost unavailable to linguists. The manuscript’s orthography and grammar reflecting the linguistic views of that time can be of great interest for those who specialize in the history of linguistic studies. The article contains another part of materiel on “M” letter. The content features of the dictionary’s publishing, the list of sources, the list of abbreviations and symbols are described in detail in the previous editions of the “PSTGU Review” serie “Philology”. Besids, all previous editions and the lists of abbreviations with the list of sources separately can be found on web-site of PSTGU